Experimental investigation on the influence of oil mist parameters on minimum quantity lubricated grinding of Inconel 751. (24th April 2014) - Balan, A.S.S.; Vijayaraghavan, L.; Krishnamurthy, R.
Minimum quantity lubrication (MQL) has a good advantage of environmental–friendly lubricating and cooling effect. This study is an experimental investigation on the significance of the MQL parameters like air pressure, oil flow rate and droplet size on grinding performance of INCONEL 751, an ideal material for high–temperature applications posing difficulties during machining, especially grinding. It was found that better results (lower grinding force, temperature and surface roughness) can be obtained for the optimal MQL condition in grinding. Also, it was found that there is hardly any crest flattening on the surface being ground with MQL technique, apart from the absence of visible grinding burns.